Al-Nahyu Dalam Istinbath Hukum - Ardiansyah, Bimas; Bakri, Muammar; Ridwan, Saleh (Media Hukum Indonesia (MHI), 2025)
This article discusses al-Nahyu in the istinbath of law. The method used refers to the literature method, where the source of data is obtained from literature materials processed through content analysis. The essence or substance of the prohibition (al-Nahyu) is inseparable from the views of several proposed scholars. The first opinion says that al-Nahyu, the substance of which is tahrim, unless there is a qarinah that turns the meaning of tahrim to others. The second opinion is the opposite by saying that basically the substance of al-Nahyu is karaha and does not indicate tahrim unless there is a qarinah that turns the meaning of karaha to tahrim and the three combinations of tahrim and karaha and does not show any meaning to one of them unless there is a qarinah. The content of the meaning of al-Nahy associated with the law of prohibition consists of haram and makruh. The three levels of law are contained in the verses of al-Nahyu which are classified as taklifi law. And mukallaf is required to carry out based on their abilities. However, it does not mean that it does not bring difficulties as a regulation that binds human behavior.